Financial Deepening in Mexico - Herman, Alexander (IMF Working Papers; Working Paper ;, 2017)
International comparisons reveal that-even controlling for a host of explanatory factors-credit depth is exceptionally low in Mexico. Using panel data methods linking credit growth and fundamentals, this paper estimates a long-term gap between actual and expected credit of about 40 percent of GDP. Possible explanations include the history of banking crises, the large informal sector and an inefficient legal system. Using a disequilibrium regression approach, this paper also finds that supply factors are particularly important as determinants of credit in Mexico. Recent financial reforms address many of the supply constraints, but their success will depend on implementation. The main challenge going forward will be to support financial deepening, while limiting risks to financial stability.